A Study on Foreign Direct Investment and Its Impact on Retailing Sector: Examining the Impact of FDI on India's Retailing Sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India has growth prospect for retail industry with a huge number ofconsumers and other favorable factors. But India’s retail market remainslargely off-limits to large international retailers like Wal-Mart, Tesco andCarrefour. Opposition to liberalizing FDI in this sector raises concerns aboutemployment losses, unfair competition resulting in large-scale exit ofincumbent domestic retailers and infant industry arguments to protect theorganized domestic retail sector that is at a nascent stage. In 2012 the IndianGovernment approved  proposal of 100 percent  FDI  inretailing  in  India subject  to certain conditions.Though this proposal  is being hailed byglobal  retail  giants, which until  now  have been  involved  in only wholesale  cash  and carry distribution  in  India and have been  longing for entry  into the  Indian retail market foryears.  The proposal has receivedvehement opposition from a spectrum of political parties in India, many of themurging for a reversal of the proposal. As a result,  the  Indian government has stalled  the implementation of  this proposalwhich has  temporarily washed off  the wishes of the  global retail  players  awaiting a  bite  of  the  Indian retail market. This paper attempts to study the present status of FDI inretailing sector in India and the impacts of FDI on various concerned segments.